Perancangan Dan Pembuatan Sistem Informasi Persediaan Barang Berbasis Microsoft Access (Studi Kasus Pada Deu Magaza) - Cintya Tresna Walidain; Mohammad Rizal Gaffar; Tangguh Dwi Pramono; Yayan Firmansyah (Ebiz Prima Nusa, 2022)
Inventory information systems are important for companies because they are used as records related to the availability of goods during sales. In Deu Magaza, the recording of goods is still done using the manual method which has many weaknesses, it is also less effective and efficient in seeing how many items are available. Therefore, a more complete and detailed information system regarding inventory is designed to assist employees in managing goods and finding available goods more easily so as to reduce errors made. The design is done using Microsoft Access to make it easier for users to learn it. Making this inventory information system helps check the availability of goods more easily and quickly, also makes work on the inventory section more effective and efficient. Evaluation of the results of the design that has been made using the usability testing method, and it is found that the design and manufacture of the information system that has been carried out is good and in accordance with the needs, can also handle the constraints that exist in the Deu Magaza inventory section.